Classical transplantation tolerance in the adult: the interaction between myeloablation and immunosuppression. - Leong, L; Qin, S; Cobbold, S; Waldmann, H (1992)
Allogeneic bone marrow transplantation in the neonate is an effective way of inducing permanent tolerance to donor tissue. To do the same in the immunocompetent adult requires immunosuppression to counter host-versus-graft alloreactivity. Conditioning with monoclonal antibodies (mAb) to CD4 and CD8 has been sufficient where donor and recipient are mismatched at only multiple "minor" histocompatibility loci, or at major histocompatibility complex (MHC) class I plus "minor" loci, but not where the mismatch involves the entire MHC. Tolerance across the MHC barrier requires extra conditioning with agents that happen to be both immunosuppressive and myeloablative, so obscuring the assessment of which effect is important. By using dimethylmyleran as a selective "space"-creating myeloablative agent, and CD4 plus CD8 mAb as sole immunosuppressive agents, we have been able to dissect the relative requirements for immunosuppression and myeloablation. We show here that transplantation tolerance could only be achieved when both types of agent were combined together so as to guarantee sufficient donor-type hemopoietic chimerism. We argue that the donor marrow, given sufficient space, will engraft and provide a sustained source of tolerogen overriding any host resistance that antibodies cannot control.